Budaya Organisasi, Kepuasan Kerja dan Komitmen Dokter Spesialis di RSUD Kota Bekasi - Sumartini, Ni Made (UI Scholars Hub, 2009)
Komitmen dokter pada rumah sakit mempengaruhi tingkat kehadiran, produktivitas dan mutu pelayanan di rumah sakit. Waktu dan tenaga yang tidak penuh diberikan dokter spesialis pada rumah sakit berpengaruh terhadap produktivitas yang kurang optimal. Tujuan penelitian ini menilai hubungan budaya organisasi, kepuasan kerja dengan komitmen dokter spesialis. Penelitian ini dilakukan pada 35 responden dokter spesialis dengan menggunakan pengukuran organinizational culture survey Denison, a job satisfaction survey Spector dan organizational commitment Allen & Meyer dengan skala yang dimodifikasi. Metoda analisis kuantitatif yang digunakan adalah univariat, bivariat dan multivariat. Sumber kepuasan dokter spesialis dengan komitmen yang tinggi adalah rekan kerja dan pekerjaan. Sumber ketidakpuasan adalah imbalan, promosi, supervisi dan kondisi kerja. Kepuasan kerja berhubungan dengan komitmen, tetapi budaya organisasi berupa praktek manajemen tidak berhubungan, karena belum terfokus pada keterlibatan, konsistensi, adaptabilitas dan penghayatan misi dokter spesialis. Dokter spesialis berhubungan dengan praktek manajemen yang terfokus pada konsistensi dan kepuasan imbalan. Komitmen normatif berhubungan dengan praktek manajemen yang fokus pada penghayatan misi dan kepuasan profesi. Physician’s commitment has significant relationship with their level of attendances, and their productivity in term of services quality, which will leverage the total quality of hospital . Objectives of this research are: examining the relationship of organization culture toward physician’s commitment; and the relationship of job satisfaction toward the physician’s commitment; the relationship of both organization culture and job satisfaction toward physician’s commitment. Method: Respondent for this research are 35. Scale of organizational culture survey Denison, scale of job satisfaction survey Spector, and scale of organizational commitment Allen & Meyer are the measurement tools. The analysis quantitative is performed in univariate, bivariate and multivariate. Results : The physician has been highly committed to RSUD Bekasi. Physician’s’s satisfaction is influent by their type of job and the relationship within their professional colleagues. Their dissatisfaction can be influent by the lack of benefit and promotion opportunities, and the non-conducive work environment conditions.The job satisfaction level has significant relationship to organization commitment. Separately, organization commitment does not have significant relate to organization culture. Organization culture, base on physician opinion, has not yet focus on empowerment; has not consistent in development of work instruction and implementation; has not adaptive with the change of organization environment; and has a lack of organization’s mission understanding. Physician’s continuans commitment has a relationship to management practices that focus on consistency and benefit . Physician’s normative commitment has a relation- ship to management practices that focus on organization mission, and their job satisfaction as a physician.